Quantitative examination of the bone health status of older adults with intellectual and developmental disability in Ireland: a cross-sectional nationwide study - Burke, Éilish (BMJ Open, 2019)
OBJECTIVES: (1) To investigate the prevalence of osteopenia and osteoporosis among adults with intellectual disabilities (IDs) and (2) to examine alternative optimal bone screening techniques. DESIGN: Observational cross-sectional study. SETTING: Wave 2 (2013–2106) of the Intellectual Disability Supplement to the Irish Longitudinal Study on Ageing. PARTICIPANTS: A national representative sample of 604 male and female persons with ID aged 43 years and over. In total, 575 participants completed quantitative ultrasound (QUS) measurements for one or both feet. OUTCOME MEASURES: Participants underwent health assessments consisting of eight objective health measures including the standardised QUS of the calcaneus bone using a GE Lunar Achilles. A preinterview questionnaire and face-to-face interview were also completed. RESULTS: Objectively QUS identified poorer rates of bone health in people with ID overall with 74% indicating evidence of osteopenia (33.2%) or osteoporosis (41%). Females scored lower than males in the QUS t-scores −2.208 (±1.77) versus −1.78(±1.734). Bone status was stratified by gender (p=0.114), age (p=0.003), level of ID (p<0.0001) and living circumstance (p<0.0001). CONCLUSIONS: This study has shown the prevalence of poor bone health in people with ID is substantial implying an increased risk of fracture due to reduced skeletal integrity. QUS screening has been shown to be useful when combined with clinical risk factors.